Ten years of rapid fertility changes in the European post - communist countries. - Sobotka, Tomas (2002)
ABSTRACT: This paper provides a detailed evidence on recent fertility changes in the countries of Central and Eastern Europe and offers an interpretation of these changes. It focuses on the ten-year period of 1989-1999, which witnessed the most intensive changes in childbearing patterns, such as rapid decline in period fertility rates, postponement of childbearing and an upsurge in the proportion of non-marital births. Changes in fertility are analyzed with the use of data collected by national statistical officers, further complemented by evidence from the FFS surveys (Fertility and Family Survey) and RHS surveys (Reproductive Health Survey). The paper discusses the notion of a socialist greenhouse - an artificial environment that shaped people's lives during the communist era. Changes in fertility and family formation over the 1990s are perceived as results of the collapse of the socialist greenhouse, which was mutually facilitated by two basic dimensions: broader social changes and new economic constraints. Particular attention is paid to the rapidly evolving differentiation of fertility patterns across Eastern Europe and the role of the cultural-religious tradition in this differentiation. Key words: Fertility, Central and Eastern Europe, Low fertility, Postponement of childbearing, Reproductive behavior, Fertility decline